Analysis of English Vocabulary in Nicolás Guillén’s Poetry - Ruiz Miyares, Leonel (2023)
The Cuban National Poet, Nicolás Guillén, has been studied by multiple specialists and critics. However, a complete study of the vocabulary of his poetry obtaining detailed statistics has not yet been carried out. Currently, the Center for Applied Linguistics of Santiago de Cuba undertakes extensive research that classifies, describes, and analyzes the different components of Nicolás Guillén's poetic vocabulary using the Natural Language Processing techniques, as part of his idiolect; and thus, detail them statistically with all their particularities. This article focuses on the description of the English vocabulary, as an integral part of the group of sublexicons that make up his poetic corpus and describes the sport semantic field present in it.